FINANCIAL PERFORMANCE CAPABILITIES AND CAPITAL EXPENDITURE IN EXPLAINING ECONOMIC GROWTH IN THE PROVINCE OF WEST KALIMANTAN - B2051142005, BUDJANG SALEH (Jurnal Ekonomi Daerah (JEDA), 2016)
Good financial management area will affect the progress of a region. Financial management conducted economically, efficiently, and effectively or fulfill the principle of value for money as well as participation, transparency, accountability, and justice will be able to boost economic growth. The level of financial ability one area can be measured from the amount of local revenue, especially revenue. Efforts to explore the ability of local governments to finance the viewable area of the financial performance measured using financial ratio analysis of local government. Measurement of financial performance in local government are also used to assess accountability and fiscal capacity in the implementation of regional autonomy. Thus, an area which otherwise good financial performance means the area has the financial ability to finance the implementation of regional autonomy.   This study aims to examine and obtain empirical evidence effect of the financial performance of local government and the allocation of capital expendituresdistrict / city in The West Kalimantan Provincial towards economic growth. Source of data used are secondary data from financial reports of local governments regency and district / city The West Kalimantan Provincial  in2010 through 2014. Analysis techniques using multiple linear regression and simple linear regression with the data processing program Eviews The results show that the degree of decentralization, effectiveness of PAD  not significant effect on capital expenditure allocationdistrict/city in The West Kalimantan Provincial,While the independen of financial and dependence of financial significant effect on capital expenditure allocation district / city in The West Kalimantan Provincial.Meanwhile, capital expenditure not significant effect on the economic growth district / city in The West Kalimantan Provincial.   Keywords : Financial Performance, Capital Expenditures, Economic Growth